Uji Potensi Metabolit Sekunder Ekstrak Kulit Buah Petai (Parkia speciosa Hassk) terhadap Kadar Kreatinin dan Ureum Tikus Secara Spektrofotometri UV-Vis: Potential Test of Secondary Metabolites Extract of Petai Fruit Peel (Parkia speciosa Hassk) on Creatinine and Ureum Levels of Rats by UV-Vis Spectrophotometry - Joni Tandi; Heru Khairul Muttaqin; Kiki Rizki Handayani; Sri Mulyani; Recky Patala (KOVALEN: Jurnal Riset Kimia, 2020)
This study aims to determine the effectiveness of bitter beans peels (Parkia speciosa Hassk) extract on creatinine and urea levels, and the effective dose of the exctract on creatinine and urea levels. This research was a laboratory experiment using 25 rats which were divided into five treatment groups, each group consisting of 5 rats. Group 1 (normal control), group 2 (negative control) were given suspension of Na-CMC, groups 3, 4, and 5 respectively given petai rind ethanolic extract doses of 300, 400 and 500 mg/kg. The results showed that petai fruit (Parkia speciosa hassk) peels extract had an effect on creatinine and urea levels of diabetes hypercholesterolemia male rats by an effective dose of 300 mg/kg which has an effect on creatinine levels by an average of 0.38 mg/dL and ureum levels by an average of 12.9 mg/dL. Keywords: petai fruit peels extract, secondary metabolite, creatinine, ureum, Streptozotocin